REINDUSTRIALIZATION OF THE EUROZONE COUNTRIES AS A PREREQUISITE FOR INDUSTRIAL RENAISSANCE OF ECONOMY IN UKRAINE - Veshko, Artem (Journal of European Economy, 2017)
This paper describes the role of industry as one of the key engines of economic growth in the countries with transition economies. The process is analyzed of change in global investment strategies, and related perspectives for reindustrialization of the European economies. The main positive and negative aspects of Ukraine as a recipient country of FDI are singled out. Empirically assessed is the relationship between FDI flows to the European countries and Ukraine.